Pengaruh Penampilan Keberagaman dalam Periklanan terhadap Minat Pembelian - Lina Budiarti; Wijayanti, Rena Feri (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
This study aims to determine the effect of the appearance of racial diversity, body type, hair type, and skin color in advertisements on purchase intention. A total of 105 questionnaires were distributed to students in Malang City who were selected using convenience sampling technique. Hypothesis testing is done by using one sample t-test. The results showed that respondents did not have a good perception of diversity in advertising, in terms of race, body type, hair type, and skin color.